1992
DOI: 10.1111/j.1471-0528.1992.tb13788.x
|View full text |Cite
|
Sign up to set email alerts
|

Is transcutaneous electrical nerve stimulation of any value during cervical laser treatment?

Abstract: Objective To assess the value of transcutaneous electrical nerve stimulation (TENS) during cervical laser therapy. Design Randomized three arm controlled clinical trial comparing (i) TENS, (ii) local anaesthetic and (iii) TENS plus local anaesthetic (direct infiltration of 2% lignocaine and 0.03 iu/ml octopressin). Setting Colposcopy Unit adapted to run randomized trials. Subjects 100 women with CIN and no previous experience of cervical surgery. Main outcome measure Visual linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In contrast, two trials found no significant differences between TENS and a group without treatment on pain intensity during flexible cystoscopy and during screening flexible sigmoidoscopy [ 37 , 38 ]. Three out of four studies reported an improvement, at least one outcome measure in favor of TENS when comparing it with a nonopioid pharmacological treatment [ 35 , 39 41 ]. To this end, one might conclude that TENS was effective in pain relief compared to placebo, no treatment, and nonopioid pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, two trials found no significant differences between TENS and a group without treatment on pain intensity during flexible cystoscopy and during screening flexible sigmoidoscopy [ 37 , 38 ]. Three out of four studies reported an improvement, at least one outcome measure in favor of TENS when comparing it with a nonopioid pharmacological treatment [ 35 , 39 41 ]. To this end, one might conclude that TENS was effective in pain relief compared to placebo, no treatment, and nonopioid pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%